Kelas Tenda Bencana (Kedana): Penerapan Model Pembelajaran Aktif Bagi Siswa Yang Terdampak Banjir bagi Sekolah-sekolah Di Kabupaten Deli Serdang Dan Kabupaten Langkat - Dedi Sahputra; Nadra Ideyani Vita; Ria Wuri Andary; Mulkan Andika Situmorang; Hartono Hartono; Habib Satria; Zulkarnain Lubis; Retna Astuti Kuswardani (Pelita Masyarakat, 2026)
The implementation of Community Service for Disaster Emergency Response (DPPM 2025) is themed "Disaster Tent Class (KENDANA)". This activity is a quick response to the impact of floods and landslides that disrupt the learning process in the Deli Serdang Regency and Langkat Regency areas. The implementation refers to the administrative and technical guidelines of the DPPM. The scope of activities includes: (1) coordination and mapping of needs with partners (schools and local governments), (2) survey of the condition of affected educational facilities, (3) implementation of emergency learning through "tent classes" and training for educators in Deli Serdang and Langkat, (4) monitoring, documentation, and handover of outputs (5) grants of emergency learning tents, study supplies and school uniforms to students (6) grants of complete drilled well packages (7) basic food assistance to the people of Sekoci Village, Besitang District, Langkat Regency. The educational materials applied are based on active and adaptive learning (ice breaking, educational games, strengthening literacy and basic numeracy) and are outlined in emergency learning modules. The activities were carried out at five schools across three districts in Deli Serdang and at one school in Sekoci Village, Besitang District, Langkat. A total of 187 students affected by the floods participated in the activities. The administrative and technical outputs submitted include emergency learning modules, participant attendance lists per location, photo and video documentation, and implementation reports per location. In substance, this program has succeeded in facilitating the return of structured learning activities at the primary and secondary levels at several locations and increasing the capacity of teachers in managing post-disaster learning.